An intervention for parents of children with epilepsy and significant learning problems: lessons learned from a feasibility study. - Buelow JM (Journal of the American Psychiatric Nurses Association)
Children with epilepsy often experience significant learning, mental health, and behavior problems that affect their quality of life. Moreover, their parents report high rates of stress. The objectives of this article are to describe the development of a theory-based cognitive behavioral intervention for parents of these children, changes made to the program based on content validity testing, and the lessons learned from implementation of a feasibility trial. The intervention was designed to foster parents' skills and confidence in advocating for their children when interacting with health care professionals and school personnel and to help parents identify community resources. Four mothers participated in the program to establish feasibility and usability. Using qualitative analysis of discussions following each phase of the intervention, we learned that parents needed more time for epilepsy education and interacting with one another and that the intervention should emphasize forming partnerships with health care and school professionals.